Long-Term Distribution, Nesting Activity, Hatching Success and Environmental Influences of the Hawksbill Turtle in Peninsular Malaysia. Part 1: A Case Study from 2015-2019 - Sarahaizad Mohd Salleh,; Shahrul Anuar Mohd Sah,; Saufi Affandi Talib,; Siti Mastura Daud,; Azizah Ibrahim, (Tropical Life Sciences Research, 2026)
Hawksbills’ (Eretmochelys imbricata) status in the state of Melaka is continuously being assessed due to Melaka being the only prominent location for hawksbills in Peninsular Malaysia. Over five years of nesting season, results of the survey revealed the cumulative nests collected the most were in Padang Kemunting and Kem Terendak with a range between 400 nests–700 nests yearly. A year-round nesting trend was observed, and the preferable peak period tends to occur between June to August almost every year. The clutch size ranged from 5 to 243 eggs over five years of the survey. An increase in temperature and rainfall amount will influence the increasing number of nests, while humidity and precipitation did not impact the nesting per month. This article presents updated nesting statistics for hawksbill turtles, showing an increase in annual nesting activity over the five-year period from 2015 to 2019 in Melaka, compared to the earlier years of 2013–2014. A greater comprehension of hawksbills’ reproductive potentiality under environmental force will aid conservation and management aims.